Synthesis of Anhydrides from Stobbe Condensation Products - Jabbar, Saba; Banerjee, Shubhra (Asian Journal of Chemistry, 2010)
Synthesis of acid-esters by Stobbe condensation of dimethylsuccinate and aldehydes or ketones, their subsequent hydrolysis to diacids and the formation of anhydrides by different reagents are reported.